A biochar loaded Ni-Co bimetallic catalyst, a preparation method thereof and application of the catalyst in hydrogen production by catalytic pyrolysis of waste plastics

CN122937795APending Publication Date: 2026-10-20NINGXIA TEACHERS UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610825546.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-09
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种生物炭负载Ni-Co双金属催化剂,旨在解决现有单金属镍基催化剂在废塑料催化热解制氢过程中因高温烧结和表面积碳导致的催化剂快速失活以及氢气选择性差、焦油产率高的问题

Benefits of technology

本发明提供的生物炭负载Ni-Co双金属催化剂在废塑料催化热解制氢中展现出显著的有益效果。该催化剂实现了废塑料向富氢气体的高效转化,大幅降低了液相焦油的生成量,显著提高了气体总收率和氢气在气相产物中的占比。同时,催化剂在高温反应条件下表现出优异的抗失活性能和结构稳定性,有效缓解了金属颗粒团聚和积碳问题。此外,本发明以农林废弃物为催化剂载体原料,实现了农业固废与废旧塑料的双重资源化利用,具有低成本、环境友好的特点,为废塑料清洁能源转化提供了具有产业化前景的解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention provides a biochar-supported Ni-Co bimetallic catalyst, its preparation method, and its application in the catalytic pyrolysis of waste plastics to produce hydrogen, belonging to the field of catalytic materials technology. The biochar-supported Ni-Co bimetallic catalyst provided by this invention can achieve efficient conversion of waste plastics into hydrogen-rich gas, significantly reducing the generation of liquid-phase tar and significantly improving the total gas yield and the proportion of hydrogen in the gaseous products. Simultaneously, the catalyst exhibits excellent resistance to deactivation and structural stability under high-temperature reaction conditions, effectively alleviating the problems of metal particle agglomeration and carbon deposition. Furthermore, this invention uses agricultural and forestry waste as the catalyst carrier raw material, realizing the dual resource utilization of agricultural solid waste and waste plastics, featuring low cost and environmental friendliness, providing a promising industrial solution for the clean energy conversion of waste plastics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalytic materials technology, and in particular to a biochar-supported Ni-Co bimetallic catalyst, its preparation method, and its application in hydrogen production from waste plastic catalytic pyrolysis. Background Technology

[0002] With the widespread use of plastic products, the disposal of waste plastics has become a global environmental challenge. Traditional landfill and incineration methods not only consume land resources but also easily generate secondary pollution. In recent years, research on converting waste plastics into high-value-added fuels or chemicals through thermochemical conversion has attracted much attention. Among them, catalytic pyrolysis for hydrogen production is a highly promising technological route, which can convert hydrocarbons in waste plastics into hydrogen-rich syngas under relatively mild conditions, realizing the energy utilization of waste.

[0003] The key to hydrogen production from waste plastic pyrolysis lies in the selection of the catalyst. Currently, commonly used catalyst systems mainly include molecular sieve catalysts, metal oxide catalysts, and supported transition metal catalysts. Molecular sieve catalysts have good shape-selective pyrolysis performance, but they are prone to rapid deactivation due to carbon deposition. Metal oxide catalysts often have low activity and require high reaction temperatures. Supported nickel-based catalysts have been extensively studied due to their excellent ability to break carbon-carbon and carbon-hydrogen bonds and are considered one of the most promising non-noble metal catalysts.

[0004] However, existing catalyst systems still face numerous challenges in the practical application of hydrogen production from waste plastic pyrolysis. The intermediate products generated from waste plastic pyrolysis are complex and easily form coke deposits on the catalyst surface, covering active sites. Furthermore, sintering of metal particles under high-temperature reaction conditions is difficult to avoid, leading to a decrease in active surface area and a shortened catalyst lifetime. Single-metal nickel-based catalysts are particularly prone to rapid deactivation due to coking and sintering, making it difficult to meet industrial requirements for hydrogen yield and selectivity. Therefore, developing novel catalysts with high activity and high stability is of great significance for promoting the practical application of hydrogen production technology from waste plastic catalytic pyrolysis. Summary of the Invention

[0005] The purpose of this invention is to provide a biochar-supported Ni-Co bimetallic catalyst, which aims to solve the problems of rapid catalyst deactivation, poor hydrogen selectivity, and high tar yield caused by high-temperature sintering and surface carbonization of existing single-metal nickel-based catalysts in the process of hydrogen production by catalytic pyrolysis of waste plastics.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a biochar-supported Ni-Co bimetallic catalyst, comprising a biochar support and a nickel-cobalt bimetallic active component supported on the biochar support. The nickel-cobalt bimetallic active component is uniformly dispersed in the form of nanoparticles on the surface and in the pores of the biochar support, and partially forms a nickel-cobalt-oxygen composite oxide solid solution.

[0007] Preferably, the biochar carrier is prepared from the pyrolysis of wild peach kernels; The mass ratio of nickel to cobalt in the nickel-cobalt bimetallic active component is 1:3 to 3:1.

[0008] Preferably, the total loading of the nickel-cobalt bimetallic active component is 10wt%~30wt%, and the size of the nanoparticles is 10nm~40nm.

[0009] This invention also provides a method for preparing a biochar-supported Ni-Co bimetallic catalyst, comprising the following steps: crushing and sieving peach kernels, then pyrolyzing them under an inert atmosphere to obtain a biochar support; dissolving nickel and cobalt precursors in a solvent, adding the biochar support, and ultrasonically impregnating it; drying and then calcining it under pulsed Joule heating in an inert atmosphere to obtain the biochar-supported Ni-Co bimetallic catalyst.

[0010] Preferably, the pyrolysis conditions are a temperature of 500°C to 600°C and a time of 120 min to 180 min, and the ultrasonic impregnation time is 20 min to 40 min.

[0011] Preferably, the drying conditions are a temperature of 80°C to 120°C and a time of 30 min to 90 min, and the pulse Joule heating conditions are a temperature of 350°C to 450°C and a time of 2 min to 5 min.

[0012] Application of the above-mentioned biochar-supported Ni-Co bimetallic catalyst or the biochar-supported Ni-Co bimetallic catalyst prepared by the above method in hydrogen production by catalytic pyrolysis of waste plastics.

[0013] The present invention also provides a method for preparing hydrogen-rich gas by pyrolysis of waste plastics, wherein the above-mentioned biochar-supported Ni-Co bimetallic catalyst is mixed with waste polyolefin plastics and reacted at high temperature in a pyrolysis reactor under an oxygen-free or inert atmosphere, and the generated gaseous products are collected.

[0014] Preferably, the waste polyolefin plastic is high-density polyethylene, low-density polyethylene, or polypropylene, and the mass ratio of the biochar-supported Ni-Co bimetallic catalyst to the waste polyolefin plastic is 1:2 to 1:8.

[0015] Preferably, the conditions for the high-temperature reaction are a temperature of 700°C to 900°C, a holding time of 10 min to 20 min, and a heating rate of 5°C / min to 15°C / min, wherein the pyrolysis reactor is a fixed-bed sliding-rail furnace, and the inert atmosphere is a nitrogen atmosphere.

[0016] The beneficial effects of this invention are: The biochar-supported Ni-Co bimetallic catalyst provided by this invention exhibits significant beneficial effects in the catalytic pyrolysis of waste plastics for hydrogen production. This catalyst achieves highly efficient conversion of waste plastics into hydrogen-rich gas, significantly reduces the generation of liquid-phase tar, and significantly improves the total gas yield and the proportion of hydrogen in the gaseous products. Simultaneously, the catalyst demonstrates excellent resistance to deactivation and structural stability under high-temperature reaction conditions, effectively mitigating the problems of metal particle agglomeration and carbon deposition. Furthermore, this invention uses agricultural and forestry waste as the catalyst carrier raw material, achieving dual resource utilization of agricultural solid waste and waste plastics, featuring low cost and environmental friendliness, and providing a promising industrial solution for the clean energy conversion of waste plastics. Attached Figure Description

[0017] Figure 1 N2 adsorption-desorption isotherms and pore size distribution diagrams of biochar prepared for different pyrolysis times, including: (a) N2 adsorption-desorption curve of BC-30; (b) pore structure diagram of BC-30; (c) N2 adsorption-desorption curve of BC-60; (d) pore structure diagram of BC-60; (e) N2 adsorption-desorption curve of BC-150; and (f) pore structure diagram of BC-150. Figure 2 Comparison of X-ray diffraction (XRD) patterns of single-metal (Ni, Co) and bimetallic (Ni-Co) catalysts; Figure 3 Scanning electron microscope (SEM) images and EDS elemental mapping diagrams of single metal (10wt%Ni@C, 10wt%Co@C) and bimetallic catalyst (10wt%Ni-10wt%Co@C); Figure 4 A comparison chart of the yields of three-phase (gas, liquid, and solid) products and the volume fractions of gaseous components (H2, CH4, C2H4, etc.) in the pyrolysis of HDPE catalyzed by monometallic and bimetallic systems. Detailed Implementation

[0018] This invention provides a biochar-supported Ni-Co bimetallic catalyst, comprising a biochar support and a nickel-cobalt bimetallic active component supported on the biochar support. The nickel-cobalt bimetallic active component is uniformly dispersed in the form of nanoparticles on the surface and in the pores of the biochar support, and partially forms a nickel-cobalt-oxygen composite oxide solid solution.

[0019] In this invention, biochar refers to a carbon-rich solid product obtained by pyrolysis and carbonization of biomass raw materials under oxygen-limited or inert atmospheres. Biochar typically possesses a highly aromatic structure, abundant surface functional groups, good thermal stability, and chemical inertness, and is widely used as a catalyst support, adsorbent, and soil conditioner. The biochar support of this invention is preferably derived from lignocellulosic biomass, whose high specific surface area and well-developed pore structure are beneficial for the loading and dispersion of active components. The nickel-cobalt bimetallic active component refers to a catalytically active material existing in the form of oxides or composite oxides of metallic nickel and metallic cobalt. Nickel is a Group VIII transition metal with excellent C-C and CH bond breaking ability, and is commonly used as an active component in hydrogenation, cracking, and reforming reactions. Cobalt is also a Group VIII transition metal, possessing the characteristics of promoting water-gas shift reactions and inhibiting carbon deposition. Nickel and cobalt have similar atomic radii and chemical properties, and readily form Ni-Co-O solid solutions during high-temperature calcination, where nickel and cobalt ions jointly occupy the cation positions in the oxide lattice, forming a homogeneous composite phase. The formation of solid solutions can effectively prevent the migration and aggregation of metal particles at high temperatures, thereby improving the thermal stability of the catalyst. The nanoparticle morphology refers to the particle size of the active component being at the nanometer level, typically between several nanometers and tens of nanometers. Uniform dispersion refers to the statistically uniform distribution of nanoparticles on the outer surface and inner walls of the internal pores of the biochar support, without obvious large-area aggregation or exposed areas. This uniform dispersion can be characterized by high-resolution electron microscopy combined with elemental surface distribution analysis. The surface and pores refer to the geometric structural characteristics of the biochar support, where the surface is the externally visible area, and the pores are internally interconnected hierarchical porous structures, including micropores, mesopores, and macropores. Partial solid solution formation means that not all nickel-cobalt species exist in solid solution form; independent NiO or CoO phases may exist, but the presence of solid solutions is a key structural basis for the synergistic effect.

[0020] Preferably, the biochar carrier is prepared by pyrolysis of wild peach kernels, and its specific surface area is greater than 1500 m². 2 / g, the mesoporous volume ratio is greater than 95%, and the mass ratio of nickel to cobalt in the nickel-cobalt bimetallic active component is 1:3 to 3:1.

[0021] Peach kernels are the shell and pit of the peach fruit, a typical agricultural and forestry waste product, characterized by their wide availability, low cost, high density, and high lignin content. The lignin content of peach kernels is generally higher than that of herbaceous biomass, and the carbon skeleton formed after pyrolysis is more dense and highly aromatic, which is beneficial for obtaining a high specific surface area and good mechanical strength. Specific surface area refers to the total surface area per unit mass of a substance, including the internal pore surface area and the external surface area, and is measured in m². 2 / g. Specific surface area greater than 1500m² 2 / g indicates that the biochar carrier has an extremely high degree of porosity, providing a large number of active sites for anchoring. Mesopores refer to pores with a diameter between 2nm and 50nm. A mesopore volume ratio greater than 95% indicates that the biochar carrier is predominantly mesoporous. This structure facilitates the entry of large molecular reactants, such as long-chain hydrocarbons produced from the pyrolysis of waste plastics, into the pores and into contact with active sites. It also facilitates the diffusion and escape of product gases, reducing carbon buildup caused by secondary reactions. The mass ratio of nickel to cobalt is a key parameter affecting the bimetallic synergistic effect. A mass ratio of 1:3 to 3:1 covers various ratios ranging from relatively more cobalt to relatively more nickel. More preferably, the mass ratio of nickel to cobalt can be 1:2 to 2:1, more preferably 1:1.5 to 1.5:1, and most preferably 1:1. An equal mass ratio of nickel to cobalt can usually maximize the synergistic effect of the two, ensuring sufficient nickel for the pyrolysis reaction and providing an appropriate amount of cobalt for the water-gas shift reaction. In addition, the ratio can be adjusted according to the type of waste plastic and reaction conditions. For example, when processing waste plastic rich in polyethylene, the ratio of nickel can be appropriately increased, and when processing polypropylene, the ratio of cobalt can be appropriately increased.

[0022] Preferably, the total loading of the nickel-cobalt bimetallic active component is 10wt%~30wt%, and the size of the nanoparticles is 10nm~40nm.

[0023] Total loading refers to the percentage of the total mass of nickel and cobalt metals in the total mass of the catalyst (including the support and active components). Too low a loading will result in insufficient active sites and insignificant catalytic effect; too high a loading will easily cause metal particle agglomeration, reducing dispersion and specific surface area. 10wt%~30wt% is a preferred range balancing activity and dispersibility. More preferably, the total loading can be 15wt%~25wt%, more preferably 18wt%~22wt%, and most preferably 20wt%. At this optimal loading, metal particles can form a monolayer or sub-monolayer dispersion on the support surface, while avoiding the formation of excessively large particles. The size of nanoparticles directly affects the number of exposed active sites and surface energy. Particle sizes of 10nm~40nm fall within the typical range of nanocatalysts. More preferably, the size of nanoparticles can be 15nm~35nm, more preferably 15nm~30nm, and most preferably 15nm~25nm. Within this size range, the particles have a high surface atomic ratio while being less prone to sintering due to excessively high surface energy. Particle size can be calculated using the full width at half maximum (FWHM) of characteristic peaks in X-ray diffraction patterns combined with the Scherrer equation, or it can be measured directly using transmission electron microscopy. Smaller particle sizes typically mean more edge and corner sites, which often exhibit higher catalytic activity.

[0024] This invention also provides a method for preparing a biochar-supported Ni-Co bimetallic catalyst, comprising the following steps: crushing and sieving peach kernels, then pyrolyzing them under an inert atmosphere to obtain a biochar support; dissolving nickel and cobalt precursors in a solvent, adding the biochar support, and ultrasonically impregnating it; drying and then calcining it under pulsed Joule heating in an inert atmosphere to obtain the biochar-supported Ni-Co bimetallic catalyst.

[0025] Crushing refers to the mechanical process of breaking large pieces of peach pits into fine particles. Common equipment includes ball mills, vibratory mills, and cutting-type crushers. Sieving involves passing the crushed material through a standard sieve of a specific mesh size to remove excessively large or small particles, obtaining powder with uniform particle size. Screens of 20 to 200 mesh are typically used. An inert atmosphere is a gaseous environment that does not participate in chemical reactions. Commonly used gases include nitrogen, argon, and helium. Its function is to prevent the raw materials from oxidizing or burning at high temperatures. Pyrolysis is the high-temperature decomposition process of organic matter under anaerobic or limited oxygen conditions. Products include solid carbon, condensable liquids, and non-condensable gases. Nickel precursors are compounds that can provide nickel ions, and cobalt precursors are compounds that can provide cobalt ions. Common forms include nitrates, acetates, chlorides, or sulfates. Solvents are liquid media that can dissolve the above precursors, typically deionized water, ethanol, or a mixture of both. Ultrasonic impregnation utilizes the cavitation effect of ultrasound to promote the diffusion of metal ions in a liquid and their penetration into the pores of a carrier. The ultrasonic frequency is typically 20kHz to 80kHz. Drying involves removing residual solvent from the impregnated material through heating; commonly used equipment includes forced-air drying ovens or vacuum drying ovens. Pulsed Joule heating utilizes the Joule heating effect to rapidly heat the material in short pulses, causing the precursor to decompose into metal oxides and anchor them on the carrier, while avoiding excessive particle growth due to prolonged high temperatures. Pulsed Joule heating is characterized by extremely rapid heating rates, extremely short holding times, and rapid cooling, which is beneficial for forming highly dispersed small-sized nanoparticles. Natural cooling involves slowly cooling the material to room temperature under an inert atmosphere after heating is stopped, preventing stress cracking or detachment of active components due to sudden cooling.

[0026] Preferably, the pyrolysis conditions are a temperature of 500°C to 600°C and a time of 120 min to 180 min, and the ultrasonic impregnation time is 20 min to 40 min.

[0027] Pyrolysis temperature is a key parameter affecting the specific surface area and pore structure of biochar. Too low a temperature results in incomplete carbonization and poor pore development; too high a temperature may lead to pore collapse and increased graphitization, thus decreasing the specific surface area. 500°C–600°C is the preferred temperature range for obtaining mesoporous biochar with a high specific surface area. More preferably, the pyrolysis temperature can be 520°C–580°C, more preferably 540°C–560°C, and most preferably 550°C. Pyrolysis time also affects the degree of carbonization and pore structure evolution. 120 min–180 min is the preferred time range for sufficient carbonization and well-developed pores. More preferably, the pyrolysis time can be 130 min–170 min, more preferably 140 min–160 min, and most preferably 150 min. Under optimal conditions, a specific surface area close to 1800 m² can be obtained. 2 The biochar support has a porosity of over 98% and a mesoporous content of approximately 98%. The duration of ultrasonic impregnation affects the uniformity and depth of metal ion penetration into the pores of the support. Ultrasonic treatment for 20-40 minutes is sufficient to achieve uniform impregnation; too short a time may lead to uneven impregnation, while too long a time offers no significant additional benefit and may increase energy consumption. More preferably, the ultrasonic impregnation time can be 25-35 minutes, with 30 minutes being the most preferred.

[0028] Preferably, the drying conditions are a temperature of 80°C to 120°C and a time of 30 min to 90 min, and the pulse Joule heating conditions are a temperature of 350°C to 450°C and a time of 2 min to 5 min.

[0029] The selection of drying temperature needs to consider the boiling point of the solvent and the thermal stability of the precursor. 80°C to 120°C is sufficient for rapid evaporation of moisture without causing nitrate decomposition. More preferably, the drying temperature can be 90°C to 110°C, and most preferably 100°C. A drying time of 30 to 90 minutes ensures sufficient removal of internal moisture from the material. More preferably, the drying time can be 45 to 75 minutes, and most preferably 60 minutes. The temperature of pulsed Joule calcination directly affects the decomposition products of the precursor and the crystal form of the metal oxides. At 350°C to 450°C, nickel nitrate and cobalt nitrate can be completely decomposed into their corresponding oxides NiO and CoO, while avoiding excessively high temperatures that could lead to particle sintering. More preferably, the calcination temperature can be 380°C to 420°C, and most preferably 400°C. A calcination time of 2 to 5 minutes is a typical short range for pulsed Joule calcination; the extremely short holding time limits the migration and growth of metal particles, which is beneficial for the formation of small-sized nanoparticles. More preferably, the calcination time can be 2.5 min to 4.5 min, more preferably 3 min to 4 min, and most preferably 3 min. This preparation method can stably obtain the above-mentioned biochar-supported Ni-Co bimetallic catalyst with specific structural and morphological characteristics.

[0030] This invention also provides the application of the above-mentioned biochar-supported Ni-Co bimetallic catalyst, or the biochar-supported Ni-Co bimetallic catalyst prepared by the above method, in hydrogen production from waste plastic catalytic pyrolysis. Working principle / mechanism explanation: Spatial obstruction and electronic effects: The introduction of Co hinders the agglomeration and growth of Ni particles at high temperatures (i.e., sintering), promoting the dispersion of metal particles. Simultaneously, charge transfer occurs between Ni and Co, optimizing the adsorption energy of reactant molecules at the active sites. Functional complementarity and relay catalysis: The unpaired electrons in the 3d orbitals of Ni species effectively reduce the activation energy of C / C bond breaking in long-chain polymers; when the generated intermediate gas encounters the Co active sites, Co strongly catalyzes the water-gas shift reaction, driving further dehydrogenation of the intermediate, thereby deeply converting macromolecules into hydrogen-rich gas, while simultaneously inhibiting the condensation polymerization of coke precursors.

[0031] In this invention, waste plastics refer to waste plastic products generated after consumption or in industry, including but not limited to packaging films, plastic bottles, plastic pipes, and agricultural mulch films. Catalytic pyrolysis refers to the thermal decomposition process of plastics in the presence of a catalyst. Compared to non-catalytic pyrolysis, catalytic pyrolysis can be carried out at lower temperatures and improves the selectivity of the target product. Hydrogen production refers to the conversion process with hydrogen as the target product. Hydrogen is a clean energy carrier, and its combustion product is only water, without producing carbon dioxide or pollutants. Applying the catalyst of this invention to the catalytic pyrolysis of waste plastics for hydrogen production can significantly increase the volume fraction of hydrogen in the gaseous products while reducing the yield of liquid tar and solid carbon residue. This application can be carried out in a fixed-bed reactor, a fluidized-bed reactor, or a moving-bed reactor, with a reaction temperature typically between 700°C and 900°C. The catalyst and waste plastics can be pre-mixed mechanically before feeding, or they can be fed separately and mixed in situ within the reactor. The reaction atmosphere is typically nitrogen, argon, or water vapor. After condensation and separation of the liquid components from the collected gaseous products, the hydrogen-rich gas can be directly burned for heating or purified for use in fuel cells, hydrogenation reactions, and other applications. This application enables the resource utilization of waste plastics and the green production of hydrogen energy, resulting in significant environmental and economic benefits.

[0032] The present invention also provides a method for preparing hydrogen-rich gas by pyrolysis of waste plastics, wherein the above-mentioned biochar-supported Ni-Co bimetallic catalyst is mixed with waste polyolefin plastics and reacted at high temperature in a pyrolysis reactor under an oxygen-free or inert atmosphere, and the generated gaseous products are collected.

[0033] Waste polyolefin plastics refer to waste plastics whose main components are polyethylene and polypropylene. These two types of plastics account for the largest proportion of waste plastics and have a high hydrogen-to-carbon ratio, making them ideal raw materials for hydrogen production. An oxygen-free or inert atmosphere means that the reaction system contains no oxygen or has extremely low oxygen content to prevent the plastic from oxidizing and burning. A pyrolysis reactor is the equipment that provides the pyrolysis environment; depending on the reactor type, it can be divided into fixed-bed, fluidized-bed, rotary kiln, screw reactor, etc. High-temperature reaction refers to operations where the reaction temperature is higher than the thermal decomposition temperature of the plastic, typically above 500°C. Collection refers to drawing the gas generated from the reaction out of the reactor outlet, pre-treating it through dust removal, condensation, and drying, and then sending it to a gas holder or directly for detection and analysis. The gaseous products mainly include small molecule gases such as hydrogen, methane, ethylene, ethane, carbon monoxide, and carbon dioxide, with hydrogen being the target product. Through the above methods, the efficient conversion of waste polyolefin plastics into hydrogen-rich gas can be achieved, and the catalyst can be reused or regenerated online.

[0034] Preferably, the waste polyolefin plastic is high-density polyethylene, low-density polyethylene, or polypropylene, and the mass ratio of the biochar-supported Ni-Co bimetallic catalyst to the waste polyolefin plastic is 1:2 to 1:8.

[0035] High-density polyethylene (HDPE) refers to polyethylene with a density of 0.94 g / cm³ or higher, characterized by a regular molecular chain structure and high crystallinity. Low-density polyethylene (LDPE) refers to polyethylene with a density between 0.91 g / cm³ and 0.94 g / cm³, characterized by a molecular chain with numerous branches. Polypropylene (PP) is an addition polymerization product of propylene, possessing high heat resistance and mechanical strength. These three plastics are typical polyolefins and are major components of waste plastics. The mass ratio refers to the mass ratio of catalyst to plastic. A mass ratio range of 1:2 to 1:8 ensures sufficient contact between catalytic active sites and the intermediate products of plastic pyrolysis without using excessive catalyst, thus avoiding increased costs. More preferably, the mass ratio of catalyst to waste polyolefin plastic can be 1:3 to 1:5, more preferably 1:3.5 to 1:4.5, and most preferably 1:4. At this optimal ratio, the mixing effect of the catalyst and plastic and the catalytic efficiency achieve the best balance.

[0036] Preferably, the conditions for the high-temperature reaction are a temperature of 700°C to 900°C, a holding time of 10 min to 20 min, and a heating rate of 5°C / min to 15°C / min, wherein the pyrolysis reactor is a fixed-bed sliding-rail furnace, and the inert atmosphere is a nitrogen atmosphere.

[0037] High-temperature reaction temperature is a key parameter affecting the degree of pyrolysis of waste plastics and the composition of gaseous products. Too low a temperature results in incomplete pyrolysis of the plastics and a high yield of liquid tar; too high a temperature may lead to excessive gas pyrolysis, causing carbon buildup or catalyst sintering. 700°C to 900°C is a preferred range balancing hydrogen selectivity and catalyst stability. More preferably, the reaction temperature can be 750°C to 850°C, more preferably 780°C to 820°C, and most preferably 800°C. The holding time refers to the time the reactor maintains the set temperature; 10 to 20 minutes is sufficient for complete pyrolysis of the plastics and for the reforming reaction to reach equilibrium. More preferably, the holding time can be 12 to 18 minutes, more preferably 13 to 17 minutes, and most preferably 15 minutes. The heating rate affects the rate of transition of the plastics from the solid phase to the gas phase and the residence time of intermediate products. A heating rate of 5°C / min to 15°C / min can avoid excessively rapid heating leading to severe foaming of the plastics or excessively slow heating leading to increased energy consumption. More preferably, the heating rate can be 8°C / min to 12°C / min, with the most preferred rate being 10°C / min. The fixed-bed sliding-rail furnace is a tubular heating furnace whose furnace body can slide along the track, thereby enabling rapid sample insertion and removal, facilitating rapid heating and cooling. Nitrogen is the most economical and readily available gas in an inert atmosphere; high-purity nitrogen with a purity of 99.99% or higher can meet the requirements for an oxygen-free reaction. Argon or helium can also be used as substitutes. Under the above preferred conditions, the highest hydrogen yield and the lowest liquid tar yield can be obtained.

[0038] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0039] Example 1 Core catalytic material: Ni-Co bimetallic oxide (mainly existing in the form of NiO and CoO, forming a composite oxide phase / solid solution).

[0040] Nanomorphology: The size of the metal nanoparticles is between 15 and 30 nm. They are uniformly attached to the surface and pore edges of the micron-sized biochar carrier, exhibiting a graded and rough "cauliflower-like" aggregated structure.

[0041] Substrate / Carrier: Amorphous carbon structure biochar derived from Prunus persica kernels (rich in aromatic ring skeletons and with strong thermal stability).

[0042] Metal loading: The mass ratio of Ni to Co is 1:1, and the total loading is 20wt% (i.e., 10wt% Ni and 10wt% Co).

[0043] This embodiment provides a method for preparing the catalyst: Impregnation-pulse Joule heating method Step 1 (Carrier Preparation): The washed and dried peach kernels were crushed and sieved, and then pyrolyzed at a specific temperature (550°C) for 150 min under a nitrogen atmosphere to obtain a biochar carrier with a high specific surface area.

[0044] Step 2 (Precursor Impregnation): Weigh out nickel nitrate hexahydrate and cobalt nitrate hexahydrate according to the calculated ratio (10wt% Ni and 10wt% Co), dissolve them in distilled water, and add the prepared biochar (e.g., 0.5g). Sonicate for 30 minutes to ensure uniform impregnation and penetration of metal ions within the carrier mesopores.

[0045] Step 3 (Drying and Calcination): Dry in a 100°C forced-air drying oven for 60 min. Then calcine at 400°C for 3 min in a nitrogen stream to pyrolyze the nitrate and form metal oxides uniformly anchored on the carbon framework in situ. After natural cooling to room temperature, the final catalyst is obtained.

[0046] Catalyst usage / testing conditions: The prepared catalyst was uniformly mixed with HDPE powder (100 mesh) at a mass ratio of 1:4.

[0047] The sample was placed in a quartz boat and subjected to catalytic pyrolysis in a fixed-bed slide rail furnace using nitrogen as the carrier gas. The preferred reaction temperature was 800°C, the heating rate was 10°C / min, and the holding time was 15min.

[0048] The product is collected as liquid tar using a condenser, and the tail gas (containing H2, CH4, C2H4, C2H6, etc.) is collected and analyzed using a gas chromatograph (GC) to calculate the yield and volume fraction.

[0049] The pyrolysis liquid yield decreased significantly to an extremely low 2.67 wt%, while the pyrolysis gas yield reached a maximum of 68.67 wt%. The H2 volume fraction in the gas phase increased dramatically to 5.99 vol.%.

[0050] To characterize the pore structure of the prepared biochar support and the phase, morphology, and catalytic performance of the catalyst, the following analyses and tests were performed: Figure 1 The N2 adsorption-desorption isotherms and pore size distributions of biochar prepared for different pyrolysis times confirm the high specific surface area and mesoporous characteristics (where (a) N2 adsorption-desorption curve of BC-30, (b) pore size distribution of BC-30; (c) N2 adsorption-desorption curve of BC-60; (d) pore size distribution of BC-60; (e) N2 adsorption-desorption curve of BC-150, and (f) pore size distribution of BC-150).

[0051] Figure 2 The X-ray diffraction (XRD) patterns of single-metal (Ni, Co) and bimetallic (Ni-Co) catalysts are compared, confirming the formation and peak broadening characteristics of the Ni-Co-O solid solution.

[0052] Figure 3 Scanning electron microscope (SEM) images and EDS elemental mapping diagrams of the single metal (10wt%Ni@C, 10wt%Co@C) and the bimetallic catalyst (10wt%Ni-10wt%Co@C) show the "cauliflower-like" morphology and uniform elemental dispersion.

[0053] Figure 4 A comparison chart of the yields of three-phase (gas, liquid, and solid) products and the volume fractions of gaseous components (H2, CH4, C2H4, etc.) in the pyrolysis of HDPE catalyzed by monometallic and bimetallic systems.

[0054] Example 2 Core catalytic material: Ni-Co bimetallic oxide (mainly existing in the form of NiO and CoO, forming a composite oxide phase / solid solution).

[0055] Nanomorphology: The size of the metal nanoparticles is between 20 and 35 nm. They are uniformly attached to the surface and pore edges of the micron-sized biochar carrier, exhibiting a graded and rough "cauliflower-like" aggregated structure.

[0056] Substrate / Carrier: Amorphous carbon structure biochar derived from Prunus persica kernels (rich in aromatic ring skeletons and with strong thermal stability).

[0057] Metal loading: The mass ratio of Ni to Co is 1:2, and the total loading is 15wt% (i.e., 5wt% Ni and 10wt% Co).

[0058] This embodiment provides a method for preparing the catalyst: The impregnation-pulse Joule heating method was adopted.

[0059] Step 1 (Carrier Preparation): The washed and dried peach kernels were crushed and sieved, and then pyrolyzed at 520°C for 170 min under a nitrogen atmosphere to obtain the biochar carrier.

[0060] Step 2 (Precursor Impregnation): Weigh out nickel nitrate hexahydrate and cobalt nitrate hexahydrate according to the calculated ratio (5wt% Ni and 10wt% Co), dissolve them in distilled water, and add the prepared biochar (e.g., 0.5g). Sonicate for 25 minutes.

[0061] Step 3 (Drying and Calcination): Dry in a 90°C forced-air drying oven for 80 min. Then calcine at 370°C for 4 min in a nitrogen stream, and naturally cool to room temperature to obtain the final catalyst.

[0062] Example 3 Core catalytic material: Ni-Co bimetallic oxide (mainly existing in the form of NiO and CoO, forming a composite oxide phase / solid solution).

[0063] Nanomorphology: The size of the metal nanoparticles is between 12 and 25 nm. They are uniformly attached to the surface and pore edges of the micron-sized biochar carrier, exhibiting a graded and rough "cauliflower-like" aggregated structure.

[0064] Substrate / Carrier: Amorphous carbon structure biochar derived from Prunus persica kernels (rich in aromatic ring skeletons and with strong thermal stability).

[0065] Metal loading: The mass ratio of Ni to Co is 2:1, and the total loading is 25 wt% (i.e., about 16.7 wt% Ni and 8.3 wt% Co).

[0066] This embodiment provides a method for preparing the catalyst: The impregnation-pulse Joule heating method was adopted.

[0067] Step 1 (Carrier Preparation): The washed and dried peach kernels were crushed and sieved, and then pyrolyzed at 580°C for 130 min under a nitrogen atmosphere to obtain the biochar carrier.

[0068] Step 2 (Precursor Impregnation): Weigh out nickel nitrate hexahydrate and cobalt nitrate hexahydrate according to the calculated ratio (16.7wt% Ni and 8.3wt% Co), dissolve them in distilled water, and add the prepared biochar (e.g., 0.5g). Sonicate for 35 minutes.

[0069] Step 3 (Drying and Calcination): Dry in a 110°C forced-air drying oven for 40 min. Then calcine in a nitrogen stream at 430°C for 2.5 min, and naturally cool to room temperature to obtain the final catalyst.

[0070] Example 4 Core catalytic material: Ni-Co bimetallic oxide (mainly existing in the form of NiO and CoO, forming a composite oxide phase / solid solution).

[0071] Nanomorphology: The size of the metal nanoparticles is between 25 and 40 nm. They are uniformly attached to the surface and pore edges of the micron-sized biochar carrier, exhibiting a graded and rough "cauliflower-like" aggregated structure.

[0072] Substrate / Carrier: Amorphous carbon structure biochar derived from Prunus persica kernels (rich in aromatic ring skeletons and with strong thermal stability).

[0073] Metal loading: The mass ratio of Ni to Co is 1:3, and the total loading is 30wt% (i.e., 7.5wt% Ni and 22.5wt% Co).

[0074] This embodiment provides a method for preparing the catalyst: The impregnation-pulse Joule heating method was adopted.

[0075] Step 1 (Carrier Preparation): The washed and dried peach kernels were crushed and sieved, and then pyrolyzed at 600°C for 120 min under a nitrogen atmosphere to obtain the biochar carrier.

[0076] Step 2 (Precursor Impregnation): Weigh out nickel nitrate hexahydrate and cobalt nitrate hexahydrate according to the calculated ratio (7.5wt% Ni and 22.5wt% Co), dissolve them in distilled water, and add the prepared biochar (e.g., 0.5g). Sonicate for 20 minutes.

[0077] Step 3 (Drying and Calcination): Dry in an 80°C forced-air drying oven for 90 min. Then calcine at 350°C for 5 min in a nitrogen stream, and naturally cool to room temperature to obtain the final catalyst.

[0078] Example 5 Core catalytic material: Ni-Co bimetallic oxide (mainly existing in the form of NiO and CoO, forming a composite oxide phase / solid solution).

[0079] Nanomorphology: The size of the metal nanoparticles is between 15 and 30 nm. They are uniformly attached to the surface and pore edges of the micron-sized biochar carrier, exhibiting a graded and rough "cauliflower-like" aggregated structure.

[0080] Substrate / Carrier: Amorphous carbon structure biochar derived from Prunus persica kernels (rich in aromatic ring skeletons and with strong thermal stability).

[0081] Metal loading: The mass ratio of Ni to Co is 1:1, and the total loading is 10wt% (i.e., 5wt% Ni and 5wt% Co).

[0082] This embodiment provides a method for preparing the catalyst: The impregnation-pulse Joule heating method was adopted.

[0083] Step 1 (Carrier Preparation): The washed and dried peach kernels were crushed and sieved, and then pyrolyzed at 500°C for 180 min under a nitrogen atmosphere to obtain the biochar carrier.

[0084] Step 2 (Precursor Impregnation): Weigh out nickel nitrate hexahydrate and cobalt nitrate hexahydrate according to the calculated ratio (5wt% Ni and 5wt% Co), dissolve them in distilled water, and add the prepared biochar (e.g., 0.5g). Sonicate for 40min.

[0085] Step 3 (Drying and Calcination): Dry in a 120°C forced-air drying oven for 30 min. Then calcine in a nitrogen stream at 450°C for 2 min, and naturally cool to room temperature to obtain the final catalyst.

[0086] Comparative Example 1 (Pure Biochar) At 800°C, the total gas yield of HDPE catalyzed by pure biochar was low, with a hydrogen content of only about 0.84 vol.%.

[0087] Comparative Example 2 (Single-metal Ni catalyst, 10wt% Ni@C) The gas yield was 50.67 wt%, and the volume fraction of H2 in the gas phase was 3.62 vol.%. When the Ni content was further increased to 15 wt%, the volume fraction of H2 plummeted to 1.73 vol. due to severe agglomeration.

[0088] As shown in the above embodiments, this invention provides a Ni-Co bimetallic catalyst using peach pit biochar as a support and its application in the catalytic pyrolysis of waste plastics to produce hydrogen. Experimental results show that, compared with the pure biochar catalytic system, the catalyst of this invention significantly improves the pyrolysis gas yield and significantly reduces the liquid tar yield. Compared with monometallic nickel-based catalysts, the bimetallic catalyst exhibits a significant advantage in the gas-phase hydrogen integral number, while effectively avoiding the problem of a sharp drop in activity caused by metal agglomeration under high loading. In summary, the catalyst of this invention maintains good catalytic activity and structural stability under high temperature conditions, verifying its feasibility and superiority in the targeted hydrogen production from waste polyolefin plastics.

[0089] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A biochar-supported Ni-Co bimetallic catalyst, characterized in that, It includes a biochar carrier and a nickel-cobalt bimetallic active component loaded on the biochar carrier. The nickel-cobalt bimetallic active component is uniformly dispersed in the form of nanoparticles on the surface and in the pores of the biochar carrier, and partially forms a nickel-cobalt-oxygen composite oxide solid solution.

2. The biochar-supported Ni-Co bimetallic catalyst according to claim 1, characterized in that, The biochar carrier is prepared by pyrolysis of peach kernels; Furthermore, the mass ratio of nickel to cobalt in the nickel-cobalt bimetallic active component is 1:3 to 3:

1.

3. The biochar-supported Ni-Co bimetallic catalyst according to claim 1, characterized in that, The total loading of the nickel-cobalt bimetallic active component is 10wt%~30wt%, and the size of the nanoparticles is 10nm~40nm.

4. A method for preparing a biochar-supported Ni-Co bimetallic catalyst, characterized in that, Includes the following steps: The peach kernels were crushed and sieved, and then pyrolyzed under an inert atmosphere to obtain a biochar carrier. Nickel and cobalt precursors were dissolved in a solvent, added to the biochar carrier, and then ultrasonically impregnated. After drying, the catalyst was subjected to pulsed Joule heating in an inert atmosphere to obtain a biochar-supported Ni-Co bimetallic catalyst.

5. The preparation method according to claim 4, characterized in that, The pyrolysis conditions are a temperature of 500°C to 600°C and a time of 120 min to 180 min, and the ultrasonic impregnation time is 20 min to 40 min.

6. The preparation method according to claim 4, characterized in that, The drying conditions are a temperature of 80°C to 120°C and a time of 30 to 90 minutes, and the pulse Joule heating conditions are a temperature of 350°C to 450°C and a time of 2 to 5 minutes.

7. The application of the biochar-supported Ni-Co bimetallic catalyst according to any one of claims 1 to 3 or the biochar-supported Ni-Co bimetallic catalyst prepared by any one of claims 4 to 6 in the catalytic pyrolysis of waste plastics to produce hydrogen.

8. A method for preparing hydrogen-rich gas by pyrolysis of waste plastics, characterized in that, The biochar-supported Ni-Co bimetallic catalyst according to any one of claims 1 to 3 is mixed with waste polyolefin plastic and reacted at high temperature in a pyrolysis reactor under an oxygen-free or inert atmosphere, and the generated gaseous products are collected.

9. The method according to claim 8, characterized in that, The waste polyolefin plastic is high-density polyethylene, low-density polyethylene or polypropylene, and the mass ratio of the biochar-supported Ni-Co bimetallic catalyst to the waste polyolefin plastic is 1:2 to 1:

8.

10. The method according to claim 8, characterized in that, The conditions for the high-temperature reaction are a temperature of 700°C to 900°C, a holding time of 10 min to 20 min, and a heating rate of 5°C / min to 15°C / min. The pyrolysis reactor is a fixed-bed sliding rail furnace, and the inert atmosphere is a nitrogen atmosphere.